PENDEKATAN DESIGN THINKING DALAM MEMAHAMI STRUKTUR ILMU PENGETAHUAN MENURUT IMAM AL GHAZALI - Agung Bayuseto; Asep Pahmi; Denden Matin Dayyin; Ghina Raudhatul Jannah; icha agustina (JURNAL YAQZHAN: Analisis Filsafat, Agama dan Kemanusiaan, 2021)
This research bases onÂ  the structure of science according to Imam Al Ghazali. Research method uses is qualitative through p Libraries and field studies with design thinking approach. The result and discussion of this research bases on science explanation, knowledge as human needs,Â  and knowledge concept according to Imam Al Ghazali. Thus, the researcher conclude that knowledge is the most important in islamic. Therefore, knowledge is primary needs for human in particularly as a caliph. In addition, knowledge is the most important for human sustainability on earth. Keyword: Design Thinking, Structure, Science, Knowledge